Visitors time cost for recreation at Larut Matang Mangrove Forest - Che Mohamad, Nor Nasuha (2016)
Larut Matang Mangrove Forest (LMMF) is rich with natural resources biodiversity and is one of the main attractions for tourism in Taiping, Perak. Starting on March of 2015, Matang Mangrove Eco-Educational Centre had charged the visitors entrance fee. The visitors are still willing to travel from a distance just to experience this opportunity. The objective of this study is to determine the characteristics of the visitors when travelling in terms of socio-demographic background, to determine the time cost involve when travel LMMF and also to determine the factors affecting the time cost when travel to LMMF Mangrove Forest. The questionnaire used for the onsite survey was designed to capture the socio-economic demand LMMF and to estimate the economic value of LMMF activity in Taiping, Perak. The count data with a sample size of 300 was modelled with a linear regression model. Based on this study, thirteen variables were tested mainly including time cost, income, on-site time, gender, marital status, age, brands, activities, quality of the places, facilities, services, conservation and occupation. The variables that influence the number of visitors for LMMF are time cost, brands and facilities. By taking the integral of the time cost model, the consumer surplus for LMMF is estimated at RM128.67per person per visit. The recreational value for LMMF for year 2015 is then estimated at RM6,168,568.47. This value implies that the opportunity cost for travelling to LMMF is valuable. This finding is vital for the stakeholder especially State of Perak Forestry Department to be use in allocation of financial resources for recreational development in LMMF.